Trabectedin in patients with advanced soft tissue sarcoma: A retrospective national analysis of the French Sarcoma Group. Issue 6 (April 2015) - Le Cesne, Axel; Ray-Coquard, Isabelle; Duffaud, Florence; Chevreau, Christine; Penel, Nicolas; Bui Nguyen, Binh; Piperno-Neumann, Sophie; Delcambre, Corinne; Rios, Maria; Chaigneau, Loic; Le Maignan, Christine; Guillemet, Cecile; et al.
Abstract Aim The French Sarcoma Group performed this retrospective analysis of the 'RetrospectYon' database with data of patients with recurrent advanced soft tissue sarcoma (STS) treated with trabectedin 1.5 mg/m2 as a 24-h infusion every three weeks. Methods Patients who achieved non-progressive disease after six initial cycles could receive long-term trabectedin treatment until disease progression. Results Overall, 885 patients from 25 French centres were included. Patients received a median of four trabectedin cycles (range: 1–28). The objective response rate was 17% (six complete/127 partial responses) and 50% (n = 403) of patients had stable disease for a disease control rate of 67%. After a median follow-up of 22.0 months, median progression-free survival (PFS) and overall survival (OS) were 4.4 and 12.2 months, respectively. After six cycles, 227/304 patients with non-progressive disease received trabectedin until disease progression and obtained a significantly superior median PFS (11.7 versus 7.6 months, P < 0.003) and OS (24.9 versus 16.9 months, P < 0.001) compared with those who stopped trabectedin treatment. Deaths and unscheduled hospitalisation attributed to drug-related events occurred in 0.5% and 9.4% of patients, respectively. Conclusion The results of this real-life study demonstrate that treatment with trabectedin of patients with STS yielded comparable or improved efficacy outcomes versus those observed in clinical trials. A long-term treatment with trabectedin given until disease progression is associated with significantly improved PFS and OS.